Evaluation of treated wastewater irrigation on the productivity of wheat - Al Hamedi, Fatima Hasan; Karthishwaran, Kandhan; Salem, Mohammed A. (Journal of Phytology, 2020)
The major objective of this research work is to propose the initial environmental impact assessment concerning the utilization of treated wastewater for two different varieties of wheat production. The study analyzed the soil chemical composition before and after irrigation at two different depths (0-30 cm & 30-60 cm). Water chemical composition is also analyzed for controlled water, treated water of Abu Dhabi and Al Ain. Wheat plant chemical composition present in the head, root, and shoot for both the varieties is analyzed. The levels of Ca, Mg, Na and CI in soil have increased after irrigation with controlled water. The presence of cations and anions in the soil are slightly higher in the treated water of Abu Dhabi. Ca, Na, CI and SO4 are found to be significantly higher after irrigation with treated wastewater of Al Ain. The plant chemical composition of head, root and shoot ND fiber, AD fiber, Crude protein and Macro elements have shown no significant differences across the three types of water and two varieties of wheat production. The correlations between RBS limits and the three types of water considered in the study are negative. The results revealed that the differences in chemical composition between RBS limits, controlled, treated wastewater of Abu Dhabi and Al Ain are statistically significant with particular reference to trace and heavy metals. Concerning water chemical composition, the study concludes that the correlation between controlled water and treated wastewater of Al Ain is strong when compared to Abu Dhabi.